(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The widespread prevalence of periodontal tissue diseases, including severe chronic generalized periodontitis, has increased interest in the use of plant-based herbal remedies for treatment due to their safety and positive outcomes [1-3].